2002
DOI: 10.4049/jimmunol.169.10.5396
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Fever-Associated Temperatures Enhance Neutrophil Responses to Lipopolysaccharide: A Potential Mechanism Involving Cell Metabolism

Abstract: Although much progress has been made in elucidating the mechanisms underlying the physiological regulation of fever, there is little understanding of the biological utility of fever’s thermal component. Considering the evolutionary co-conservation of fever and innate immunity, we hypothesize that fever’s thermal component might in general augment innate immune function and, in particular, neutrophil activation. Accordingly, we have evaluated the effect of febrile temperatures on neutrophil function at the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Finally, maintaining a normal core body temperature (36.6 Ϯ 0.5°C) after anesthesia has been shown to decrease the incidence of infectious complications in patients undergoing colorectal resection (16). Among the mechanisms suggested in the antibacterial effect of heating, augmentation of the innate immune function is probably the most intensively studied (9,10,17,19,27). Though our results demonstrate that the application of AMFields and sham heat did not cause an increase in lung temperatures, these treatments did raise the temperature of the peripheral organs of the treated mice by at least 2 degrees (the normal skin temperature of mice is 34 to 35°C, while in the present study, the electrode temperature was set to 37°C).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, maintaining a normal core body temperature (36.6 Ϯ 0.5°C) after anesthesia has been shown to decrease the incidence of infectious complications in patients undergoing colorectal resection (16). Among the mechanisms suggested in the antibacterial effect of heating, augmentation of the innate immune function is probably the most intensively studied (9,10,17,19,27). Though our results demonstrate that the application of AMFields and sham heat did not cause an increase in lung temperatures, these treatments did raise the temperature of the peripheral organs of the treated mice by at least 2 degrees (the normal skin temperature of mice is 34 to 35°C, while in the present study, the electrode temperature was set to 37°C).…”
Section: Discussionmentioning
confidence: 99%
“…These animals were not only subjected to a greater intrapulmonary PMN burden, but they also were exposed to higher levels of the PMN activating cytokines, GM-CSF, KC, MIP-2, and IL-1␤. Furthermore, FRH itself directly enhances PMN generation of reactive oxygen intermediates and NO responsiveness to LPS (48). In fact, we previously reported that immunoblockade of the common receptor for KC and MIP-2 in hyperoxia-exposed mice partially reversed the accelerated death caused by coexposure to FRH (24).…”
Section: Figurementioning
confidence: 90%
“…The febrile rise in body temperature could exert beneficial effects for the host by enhancing immune cell activities (138) and making the internal thermal environment out of the temperature range optimal for pathogen growth (90). Increase in body temperature similar to fever is also observed when animals receive psychological stress.…”
mentioning
confidence: 94%